The Analysis of Clearance and Ports Equipment Toward Long Container Dwelling Time (Case Study: KPP Bea Cukai Tanjung Emas and Semarang Container Terminal) - Utami, Erita; Sulistiyani, Endang; Azizah, Azizah (Jurnal Manajemen Bisnis, 2020)
The aim of this study is to examine the effect of clearance and port equipment on long container dwelling time both partially and simultaneously. The study utilized quantitative research method. Secondary data which used were monthly period data from January 2016 – March 2019. The data sources were from PT. Pelabuhan Indonesia III (Persero) Semarang Container Terminal and Tanjung Emas Custom and Excises. Regarding the use of period, the total data which used is thirty-nine months. The study explored with multiple linear regression statistical analysis. The t-Test result informed that clearance has significant effect on long container dwelling time. Meanwhile, the port equipment has no significant effect on long container dwelling time. Both clearance and port equipment has significant effect simultaneously. Clearance gives a dominant influence on container waiting time From the result, suggestions that can be taken are conducting the Focus Group Discussion of Indonesia National Single Window, add more equipment, avoid the breakdown equipment together with maintenance schedule, provide operator training, and benchmark to other port companies.